Pectin methylesterase and pectin remodelling differ in the fibre walls of two gossypium species with very different fibre properties. - Qinxiang Liu (Public Library of Science (PLoS), 2013)
Pectin, a major component of the primary cell walls of dicot plants, is synthesized in Golgi, secreted into the wall as methylesters and subsequently de-esterified by pectin methylesterase (PME). Pectin remodelling by PMEs is known to be important in regulating cell expansion in plants, but has been poorly studied in cotton. In this study, genome-wide analysis showed that PMEs are a large multi-gene family (81 genes) in diploid cotton (Gossypium raimondii), an expansion over the 66 in Arabidopsis and suggests the evolution of new functions in cotton. Relatively few PME genes are expressed highly in fibres based on EST abundance and the five most abundant in fibres were cloned and sequenced from two cotton species. Their significant sequence differences and their stage-specific expression in fibres within a species suggest sub-specialisation during fibre development. We determined the transcript abundance of the five fibre PMEs, total PME enzyme activity, pectin content and extent of de-methylesterification of the pectin in fibre walls of the two cotton species over the first 25-30 days of fibre growth. There was a higher transcript abundance of fibre-PMEs and a higher total PME enzyme activity in G. barbadense (Gb) than in G. hirsutum (Gh) fibres, particularly during late fibre elongation. Total pectin was high, but de-esterified pectin was low during fibre elongation (5-12 dpa) in both Gh and Gb. De-esterified pectin levels rose thereafter when total PME activity increased and this occurred earlier in Gb fibres resulting in a lower degree of esterification in Gb fibres between 17 and 22 dpa. Gb fibres are finer and longer than those of Gh, so differences in pectin remodelling during the transition to wall thickening may be an important factor in influencing final fibre diameter and length, two key quality attributes of cotton fibres.